Academic Genres and Federal State Educational Standard: on Course to Compromise - N. I. Kolesnikova; M. G. Malinina; Y. V. Ridnaya (Научный диалог, 2017)
The article is devoted to the organization of work with postgraduate students of Russian universities. The urgency of the problem of teaching the principles of presentation of results of own research activities in written and oral form in Russian and foreign (English) languages is stated. The authors consider the generalization of learning objectives and equivalence of requirements for the mastery of the mother tongue and a foreign language in a modern high school standards at the stage of bachelor, master and PhD programs one of the important reasons that hinder the solution to the problem. Uneven number of hours distinguished for studying of Russian and foreign languages starting from the senior secondary school is also noted. Based on their long-time experience, the authors set out their vision of ways of solving this problem for the Russian audience. As a compromise in the existing conditions it is proposed to introduce for these categories of students the new integrated, bilingual course. The aim of the course is to help postgraduate students of different specialties in the preparation and publication of scientific works in Russian and English and to enable them part-time and full-time participation in conferences of Russian and international level. The choice of the course name and the components of its content is carried out taking into account the analysis of foreign experience and Russian rhetorical tradition. The authors’ development of the modules of the course “Scientific writing and scientific rhetoric” is presented, a brief description of their contents is given.